2016
DOI: 10.7717/peerj.2728
|View full text |Cite
|
Sign up to set email alerts
|

Flexible ureteroscopy for renal stone without preoperative ureteral stenting shows good prognosis

Abstract: PurposeTo clarify the outcome of flexible ureteroscopy (fURS) for management of renal calculi without preoperative stenting.MethodsA total of 171 patients who received 176 fURS procedures for unilateral renal stones were reviewed. All procedures were divided into two groups depending on whether they received ureteral stenting preoperatively. Baseline characteristics of patients, stone burden, operation time, stone-free rates, and complications were compared between both groups.ResultsSuccessful primary access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 26 publications
7
40
0
Order By: Relevance
“…Previous studies reported high insertion rate and low complication rate of UAS in the PS system [1,4,7,8]. However, successful insertion of UAS for NPS group was still not good enough with a failure rate of almost 10% in low complication study [8]. Our data showed some interesting findings of an intentional PS.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies reported high insertion rate and low complication rate of UAS in the PS system [1,4,7,8]. However, successful insertion of UAS for NPS group was still not good enough with a failure rate of almost 10% in low complication study [8]. Our data showed some interesting findings of an intentional PS.…”
Section: Discussionsupporting
confidence: 66%
“…UAS via a guide wire was recommended by EAU guidelines in the practice of fURS, with decreased risk of ureteral damage and easy multiple access to the upper urinary tract. Previous studies reported high insertion rate and low complication rate of UAS in the PS system [1,4,7,8]. However, successful insertion of UAS for NPS group was still not good enough with a failure rate of almost 10% in low complication study [8].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The mean size of stones in 5 studies was more than 20 mm. However, preoperative stenting is frequently used to allow passive ureteral dilatation, which is supposed to facilitate the passage of a flexible ureteroscope or ureteral access sheath [40] . At this point, one fact that cannot be ignored is that ESWL may result in additional stent-related complications compared to PCNL or LU, which not need use a preoperative stent.…”
Section: Discussionmentioning
confidence: 99%